2009
DOI: 10.7705/biomedica.v29i4.140
|View full text |Cite
|
Sign up to set email alerts
|

Actividad inducida por androsterona y hemisuccinato de androsterona sobre la presión de perfusión y la resistencia vascular

Abstract: Introducción. Existen pocos datos sobre los efectos de la androsterona y sus derivados a nivel cardiovascular. Además, el mecanismo molecular de estos andrógenos y su sitio de acción celular son poco claros. Objetivo. Evaluar el efecto inducido por la androsterona y el hemisuccinato de androsterona sobre la presión de perfusión y la resistencia vascular. Materiales y métodos. Los efectos de la androsterona y del derivado de androsterona sobre la presión de perfusión y la resistencia vascular fueron evaluados e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The compounds N 1 -(2,3-dimethoxystrychnidin-10-yliden)ethane-1,2-diamine (1) and androsteron-ehemisuccinate (2) were prepared according to a previously reported method of Figueroa 10,12 . The other compounds evaluated in this study were purchased from Sigma-Aldrich Co. Ltd.…”
Section: Methodsmentioning
confidence: 99%
“…The compounds N 1 -(2,3-dimethoxystrychnidin-10-yliden)ethane-1,2-diamine (1) and androsteron-ehemisuccinate (2) were prepared according to a previously reported method of Figueroa 10,12 . The other compounds evaluated in this study were purchased from Sigma-Aldrich Co. Ltd.…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that indomethacin did not block the effects of estradiol-ethylenediamine derivative, suggesting that mechanism was not via prostanglandins synthesis and secretion. Analyzing these data and reports indicating that the effect of a number of steroids on blood pressure involves activation of the calcium channel 37 , we used nifedipine an L-type calcium channel inhibitor. The results showed that the activity of estradiol-ethylenediamine derivative was significantly blocked by nifedipine.…”
Section: Discussionmentioning
confidence: 99%